THE FORMS OF EDUCATIONAL EXPERTS TRAINING IN GERMAN-SPEAKING COUNTRIES OF THE EUROPEAN UNION - Наталія Пономаренко (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2015)
The article covers the main forms of educational experts training in Germany, Austria and Switzerland. It has been found that in order to train educational experts, universities and higher schools of pedagogical education in these countries offer Master's Programmes, in particular: the Free University of Berlin , Germany; the Higher Pedagogical school of Weingarten, Germany; the Higher Pedagogical school of Vorarlberg, Austria; the Higher Pedagogical school of Sankt-Gallen, Switzerland; the Higher Pedagogical school of Schaffhausen, Switzerland; the Higher Pedagogical school of Thurgau, Switzerland. The main forms of the educational process are lectures, seminars, project seminars, research workshops, colloquia, practical training, project work and Master's research paper. The Master's programmes also include some elements of distance education. Educational experts training is also carried out by those institutions that monitor and support the development of education, for instance, The State Institute for School Quality and Education Research, Bavaria as well as quality control agencies (Qualitätsagenturen). The main forms of education are seminars (from one-day to one-week long), and one or two-days training courses.